SNI ISO/IEC 27001 dan Indeks KAMI: Manajemen Risiko PUSDATIN (PUPR) - Piski Sundari; Wella Wella (Universitas Multimedia Nusantara, 2021)
Pusdatin of the Ministry of Public Works and Public Housing is an institution that manages data and information to support management within the ministry of public works. This research was conducted to evaluate the maturity of agencies prior to conducting an external audit of ISO 27001: 2013 certification. The method used in this research is PDCA (Plan-Do-Check-Act) using our index and ISO 27001, the technicality of this research starts from a check for analysis of current conditions, Act is carried out for assessment of the WE index, Plan compares our index results with ISO 27001, and Do control recommendations for improvement. The results of this evaluation show that PUSDATIN stopped at level I + in yellow area and overall PUSDATIN stated,